Correspondence of Florence O'Donoghue with various individuals regarding Tomás MacCurtain and O'Donoghue's book about him, - O'Donoghue, Florence, 1895-1967 (1954)
Correspondents include Annie MacSwiney, Cornelius Kelliher, Seán Murphy and Martin A. Harvey.